SHAYKH ‘ABDUL QADIR BIN ‘ABDUL RAHIM BUKIT BAYAS DAN KITABNYA RISALAH FI BAYAN HUKM AL-BAY’ WA AL-RIBA: SATU SOROTAN: Shaykh ‘Abdul Qadir Bin ‘Abdul Rahim Bukit Bayas and His Book (Risalah fi Bayan Hukm al-Bay’ wa al-Riba): A Review - Mohd, Hasanuldin; Ali, Abdul Karim (Jurnal Syariah, 2012)
In the past, Malay Muslims contributed by enriching the collection of writings. Among them is Shaykh ‘Abdul Qadir bin ‘Abdul Rahim Bukit Bayas. His book, entitled Risalah Fi Bayan Hukm Al-Bay’ Wa Al-Riba is an essential reference, particularly in discussing Fiqh al- Mu’amalat. This study will attempt to highlight the author’s biodata and the history of the book, how the manuscript is tracked, as well as analysing the content of his book. The data were collected from library research, documentation method and interviews. Then, they were analysed by analysis content method. The study found that Shaykh is one of the Malay scholars who played a role in delivering the Fiqh al-Mu’amalat in the local mould. In conclusion, the author is considered to be an influential scholar in Terengganu although he is not so famous.